2009
DOI: 10.1016/j.ejvs.2008.12.026
|View full text |Cite
|
Sign up to set email alerts
|

The Residual Risk of Cerebral Embolism after Carotid Stenting: The Complex Interplay between Stent Coverage and Aortic Arch Atherosclerosis

Abstract: The extent of the stent neo-intimal formation is independent of stent type, but it is correlated with proximal plaque coverage. Six months after CAS, MESs are still possible and are not prevented by complete neo-intimal stent coverage. Complicated aortic arch atherosclerosis is an independent predictor of late MES, thus underlying its importance in cerebral ischaemia onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Most of these DWI-positive spots are asymptomatic, with only about 15% of the patients develop TIAs or stroke 3,[6][7][8][9][10][11] . Moreover, the evidence from TCD monitoring studies has confirmed that the embolic debris can be generated at all stages of the procedure, including the placement of the guiding catheter, before and after the placement of embolic protection devices 11,12 , angioplasty, the deployment of stent, and even in the weeks following successful stenting 3,8,[13][14][15][16][17][18] . Most of these studies focused on the MRI or TCD findings related to the morbidity or mortality of CAS, or the effect of embolic protective devices.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these DWI-positive spots are asymptomatic, with only about 15% of the patients develop TIAs or stroke 3,[6][7][8][9][10][11] . Moreover, the evidence from TCD monitoring studies has confirmed that the embolic debris can be generated at all stages of the procedure, including the placement of the guiding catheter, before and after the placement of embolic protection devices 11,12 , angioplasty, the deployment of stent, and even in the weeks following successful stenting 3,8,[13][14][15][16][17][18] . Most of these studies focused on the MRI or TCD findings related to the morbidity or mortality of CAS, or the effect of embolic protective devices.…”
Section: Introductionmentioning
confidence: 99%